Climate emergency: lessons from the Covid-19 emergency?. (2nd January 2020) - Sugden, David; Werritty, Alan; Webb, Janette; Kerr, Andy
ABSTRACT : The COP-26 United Nations Climate Change meeting, scheduled to be held in Glasgow in 2021, is an important step in the world's attempt to deal with the climate emergency arising from increasing greenhouse gas emissions. Here we look at how society has responded to the Covid-19 emergency and compare it with the response to the climate change emergency, the latter based on our experience of a Royal Society of Edinburgh Inquiry on climate change published nearly ten years ago (RSE, 2011). With reference to Covid-19, civil society's response to the lockdown showed the power of clear political leadership and also the willingness of people to work together. On the negative side, the UK national test and trace system struggled because of a disconnect between national and regional activities. In our climate change report, we identified similar organisational barriers that were impeding a move towards a low-carbon future, especially the lack of responsibilities and powers at a city regional scale. If Scotland is to reduce emissions seriously, the focus needs to be on transport (30% of emissions), heating and agriculture. Without more responsibility and power at a city regional scale, Scotland will not achieve its emissions targets.